Effectiveness of Solution-Focused Brief Counseling and Motivational Interviewing in Improving Students’ Self-Disclosure - Indriani, Iftitah; Wibowo, Mungin Eddy; Mulawarman, Mulawarman (Jurnal Kajian Bimbingan dan Konseling, 2022)
This study investigates the effectiveness of solution-focused brief counseling and motivational interviewing in enhancing students’ self-disclosure. This study used a randomized pretest-posttest control group design. The sixteen participants from State Junior High School 3 Comal, Indonesia, were selected through nonprobability sampling with purposive sampling. The participants were divided into experiment and control groups. For the research instruments, this study used The Self-Disclosure Questionnaire developed by Jourard to measure students’ self-disclosure. The obtained data were analyzed using the repeated measures ANOVA test. Our analysis results showed that solution-focused brief counseling and motivational interviewing were effective in improving students’ self-disclosure. Therefore, the school counselor can implement both solution-focused brief counseling and motivational interviewing to enhance their students’ internal potential and self-disclosure. Future studies are suggested to widen the research participants and analyze the effects of gender and age differences on the effectiveness of solution-focused brief counseling and motivational interviewing in improving students’ self-disclosure.